The Long-Run Impacts of Adolescent Drinking: Evidence from Zero Tolerance Laws - Tatiana Abboud; Andriana Bellou; Joshua Lewis (Institute of Labor Economics (IZA), 2019)
This paper provides the first long-run assessment of adolescent binge drinking on later- life health and labor market outcomes. Our analysis exploits cross-state variation in the rollout of "Zero Tolerance" (ZT) Laws, which set strict alcohol limits for drivers under age 21 and led to sharp reductions in youth binge drinking. We adopt a difference-in-differences approach that combines information on state and year of birth to identify individuals exposed to the laws during adolescence and tracks the evolving impacts into middle age. We find that ZT Laws led to significant improvements in later-life health. Individuals exposed to the laws during adolescence were substantially less likely to suffer from cognitive and physical limitations in their 40s. The health effects are mirrored by improved labor market outcomes. These patterns cannot be attributed to changes in educational attainment or marriage. Instead, we find that affected cohorts were substantially less likely to drink heavily by middle age, suggesting an important role for adolescent initiation and habit-formation in affecting long-term substance use.
Keywords: I18; I12; J20; 330; Zero Tolerance Laws; binge drinking; disabilities; substance abuse